2019
DOI: 10.1111/jfbc.13067
|View full text |Cite
|
Sign up to set email alerts
|

Sika deer antler protein against acetaminophen‐induced oxidative stress and apoptosis in HK‐2 cells via activating Nrf2/keap1/HO‐1 pathway

Abstract: Nf-E2-related transcription factor 2 (Nrf2) helps cells fight oxidative stress events in vivo and in vitro by promoting the expression of antioxidants and detoxification enzymes. The necessary factors regulating Nrf2 activity and stability during analgesic nephropathy are not fully understood. Our results suggest that acetaminophen produces nephrotoxicity in HK-2 cells by inhibiting keap1 degradation. APAP subsided Nrf2 nuclear accumulation by inhibition of keap1 degradation, thereby reducing the binding of Nr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…To further elucidate this antioxidant action, the methionine availability of RP on the activation of the Nrf2‐ARE pathway was also emphasized in this study. Nrf2 can activate and upregulate ARE‐driven detoxification and antioxidant expression, exerting an endogenous antioxidant defense system (Han et al, 2019; Jaisupa et al, 2018; Li et al, 2016; Nguyen, Nioi, & Pickett, 2009; Ruan et al, 2019; Suzuki & Yamamoto, 2015). Hence, the activation of the Nrf2‐ARE pathway plays a critical role in scavenging ROS.…”
Section: Discussionmentioning
confidence: 99%
“…To further elucidate this antioxidant action, the methionine availability of RP on the activation of the Nrf2‐ARE pathway was also emphasized in this study. Nrf2 can activate and upregulate ARE‐driven detoxification and antioxidant expression, exerting an endogenous antioxidant defense system (Han et al, 2019; Jaisupa et al, 2018; Li et al, 2016; Nguyen, Nioi, & Pickett, 2009; Ruan et al, 2019; Suzuki & Yamamoto, 2015). Hence, the activation of the Nrf2‐ARE pathway plays a critical role in scavenging ROS.…”
Section: Discussionmentioning
confidence: 99%
“…뿐만 아니라 염 증에 대한 기전 이외에 미토콘드리아 기능 부전과 저산소증 의 개선을 목표로 한약제제의 사용도 고려될 수 있다. 인 삼 [82][83][84][85][86][87] , 황기 [88][89][90] , 녹용 [91][92][93][94]…”
Section: 롱코비드로 인한 비만의 한의학적인 치료를 위한 제언unclassified
“…Nrf2 induction suppressing TXNIP/NLRP3 signaling is not only associated with elimination of ROS, but also enhanced transcription of TRX-1 [ 10 ]. It has been reported that induction of Nrf2 exerts protective effects against oxidative stress, inflammation, and apoptosis in the progress of renal injury in vivo and in vitro model of APAP-AKI [ 4 , 11 ]. In addition, NLRP3 inflammasome activation exists in APAP-AKI and inhibition of NLRP3 can alleviate renal injury [ 12 ].…”
Section: Introductionmentioning
confidence: 99%